Advances in the search for the effectiveness of the process and the efficiency of judicial action:: the experience of the Federal Regional Court of the 3rd Region (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article deals with one of the greatest challenges of the Judiciary, which is to give an adequate response to the growing expansion of access to justice, with the guarantee of the reasonable duration of the process. To this end, considering that the principles of access to justice and due process of law have been gaining new contours, the study aims to present the advances in the search for the effectiveness of the process and the efficiency of judicial action. In this regard, addresses the Judicial Reform and the contribution of the National Council of Justice to the modernization of the judiciary. It then analyzes the experience of the Federal Regional Court of the 3rd Region, noting that the Federal Court of the 3rd Region was a pioneer in Brazil with regard to the adoption and implementation of electronic processes on a large scale. In this regard, in addition to the implementation of the PJe, it presents other precursor initiatives such as those related to the Innovation Laboratories of the Judiciary, the SIGMA and SINARA projects, virtual trial sessions and oral arguments by videoconference, the tool to facilitate the receipt of RPVs in the Courts, the conciliation platform for solving cases related to Covid-19, ending with the issue of building innovative solutions to deal with the judicialization of sensitive issues during the pandemic.
Keywords: Reform of the Judiciary; Access to Justice; Reasonable duration of the process; Effectiveness; Efficiency; Electronic Judicial Process; Innovation; Pandemic